The Association between Benzene and Congenital Anomalies in Oklahoma, 1997-2009 - Janitz, Amanda E. (Occup Environ Med, 2018)
OBJECTIVES: Although the most common cause of death in infants, little is known about the etiology of congenital anomalies. Recent studies have increasingly focused on environmental exposures, including benzene. While benzene is known to affect the central nervous system, the effects on the developing fetus are unclear. METHODS: We conducted a retrospective cohort study to evaluate the association between ambient benzene exposure and the prevalence of congenital anomalies among 628,121 singleton births in Oklahoma from 1997–2009. We obtained benzene from the Environmental Protection Agency’s 2005 National-Scale Air Toxics Assessment for the census tract of the birth residence. We used modified Poisson regression with robust standard errors to calculate prevalence proportion ratios (PPR) and 95% confidence intervals (CI) between quartiles of benzene exposure and critical congenital heart defects (CCHDs), neural tube defects (NTDs), and oral clefts adjusted for maternal education and tobacco use. RESULTS: Median benzene exposure concentration in Oklahoma was 0.57 μg/m(3). We observed no association between benzene exposure and oral clefts, CCHDs or NTDs. When specific anomalies were examined, we observed an increased prevalence of cleft lip among those exposed to the second quartile of benzene compared to the first (PPR: 1.50, 95% CI: 1.05, 2.13), though no association with higher levels of exposure. CONCLUSIONS: Our findings do not provide support for an increased prevalence of anomalies in areas more highly exposed to benzene. Future studies would benefit from pooling data from multiple states to increase statistical power and precision in studies of air pollutants and specific anomalies.